2018
DOI: 10.1002/imhj.21696
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in Infants With Cleft Lip and/or Palate: Marginal Security and Its Changes Over Time

Abstract: This study examines the attachment quality and how this changed over time among infants who had cleft lip and palate (CLP), by conducting a prospective longitudinal study addressing the effects of this type of perinatal event on the parent-infant relationship and the emotional development of the infants. At 12 months of age, the Strange Situation Paradigm (SSP; M. Ainsworth, M.C. Blehar, E. Waters, & T. Wall, 1978) was administered to a sample of 38 CLP infants (born between 2003 and 2010) and 17 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Boztepe et al also indicated that, in comparison with congenital heart disease, cleft lip was more likely to adversely affect maternal emotional connection toward the infant possibly due to the visual aspects of the condition [12]. Indeed, there is increasing evidence suggesting potential impairments of infant-maternal relationships among children with CL/P [1315]. However, the association of childbirths of infants with CL/P on maternal emotional involvement toward infants still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Boztepe et al also indicated that, in comparison with congenital heart disease, cleft lip was more likely to adversely affect maternal emotional connection toward the infant possibly due to the visual aspects of the condition [12]. Indeed, there is increasing evidence suggesting potential impairments of infant-maternal relationships among children with CL/P [1315]. However, the association of childbirths of infants with CL/P on maternal emotional involvement toward infants still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations have been reported with maternal AAIs, children’s self-representations and social competence at school. The ASCT has also been used in clinical group of children, such as children with cleft lip and/or palate in a recent longitudinal study [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Boztepe et al also indicated that, in comparison with congenital heart disease, cleft lip was more likely to adversely affect maternal emotional connection toward the infant possibly due to the visual aspects of the condition [12]. Indeed, there is increasing evidence suggesting potential impairments of infant-maternal attachments among children with CL/P [13][14][15]. However, the impact of CL/P birth on maternal emotional involvement toward infants still remains unclear.…”
Section: Introductionmentioning
confidence: 99%